Photochemical Studies of Isolated Phenanthroline Adduct of Bis(4,4,6-trimethyl-1,3,2-dioxaphosphorinane-2-thione-2-thiolato) Nickel(II), its Formation under Photo-irradiation and Formation of β and γ-Picoline Adducts of Bis(4,4,6-trimethyl- 1,3,2-dioxa - Dave, R.S.; Bhasin, C.P. (Asian Journal of Chemistry, 2016)
On irradiation with visible light six coordinated octahedral phenanthroline adduct of nickel(II) bis(O,O-hexylene dithiophosphate) is converted into five coordinated trigonal-bipyramidal complex. Four coordinated nickel(II) bis(O,O-hexylene dithiophosphate) on reaction with phenanthroline under photo-irradiation forms five-coordinated complex again. In contrast to the above, four-coordinated bis(O,O-hexylene dithiophosphate) nickel(II) on reaction with β and γ-picolines under photo-irradiation forms six-coordinated complexes.